Recent advances in cancer research and therapy - Liu, Xin-Yuan, 1927-; Pestka, Sidney; Shi, Yufang, 1960-; ScienceDirect eBooks (Burlington : Elsevier Science, 2012)
Cancer continues to be one of the major causes of death throughout the developed world, which has led to increased research on effective treatments. Because of this, in the past decade, rapid progress in the field of cancer treatment has been seen. Recent Advances in Cancer Research and Therapy reviews in specific details some of the most effective and promising treatments developed in research centers worldwide. While referencing advances in traditional therapies and treatments such as chemotherapy, this book also highlights advances in biotherapy including research using Interferon and Super.
Note continued: 15.5. Future Perspective -- Integration of TCM with Modern Medicine Both in Experimental and in Clinical Study -- 16. Effect of Arsenic Trioxide on Acute Promyelocytic Leukemia and Glioma: Experimental Studies, Clinical Applications, and Perspectives / Bao-Feng Yang -- 16.1. Historical Perspectives of Arsenic Derivatives in Medicine -- 16.2. Effect of Arsenic Trioxide in APL -- 16.2.1. What Is the Role of Arsenic in Newly Diagnosed APL? -- 16.2.2. Conclusion and Perspectives: Can We Induce a 100% CR Rate in Newly Diagnosed APL? -- 16.3. The Application of Arsenic Trioxide in Glioma -- 16.3.1. Characteristics of Glioma -- 16.3.2. Experimental Studies -- 16.3.3. Clinical Application -- 16.3.4. Perspectives -- 16.4. Experimental Studies and Clinical Applications of As2O3 in Harbin Medical University -- 16.5. Conclusions -- 17. Recent Advances in Nasopharyngeal Carcinoma Research and Its Pathogenesis / Kai-tai Yao -- 17.1. Introduction -- 17.2. Molecular Pathogenesis of NPC -- 17.2.1. Genetic Factor and NPC Susceptibility -- 17.2.2. EBV and NPC -- 17.3. Molecular Diagnosis of NPC -- 17.3.1. Discovery of Molecular Biomarker of NPC -- 17.3.2. Application of Molecular Diagnosis in NPC -- 17.4. Advances in the Treatment of NPC -- 17.4.1. Clinical Application of Cytotoxic Therapeutics -- 17.4.2. Targeted Therapy -- 17.4.3. Immunotherapy -- 17.4.4. Gene Therapy -- 17.5. Summary -- 18. Esophageal Carcinoma / Jie Shen -- 18.1. An Overview of Esophageal Carcinoma -- 18.1.1. Epidemiology -- 18.2. The Pathogenesis of Esophageal Carcinoma -- 18.2.1. The Pathogenesis of Barrett's Esophagus -- 18.2.2. The Pathogenesis of Esophageal Carcinoma -- 18.3. The Etiopathogenesis of Esophageal Carcinoma -- 18.3.1. Diet, Smoking, and Intemperance -- 18.3.2. Genetics and Genes -- 18.3.3. Virus and Inflammation -- 18.4. The Treatment of Esophageal Carcinoma -- 18.4.1. Anatomy -- 18.4.2. Histology -- 18.4.3. Clinical Presentation -- 18.4.4. Diagnostic Work-Up -- 18.4.5. Stage -- 18.4.6. Treatment -- 18.5. The Prevention of Esophageal Carcinomas -- 18.5.1. Protecting the Esophagus by Changing Poor Diet and Living Habits -- 18.5.2. Reducing the Intake of Nitrosamines -- 18.5.3. The Significance of Balanced Nutrition -- 18.5.4. The Active Treatment of Esophageal Epithelial Hyperplasia and Severe Esophagitis -- 18.5.5. The Identification of the Genetic Susceptibility to Esophageal Cancer Among Groups or Individuals -- 19. Research on Colorectal Cancer in China / Qi Dong -- 19.1. The Progress of Epidemiological Study on CRC -- 19.1.1. Introduction -- 19.1.2. Distribution of CRC -- 19.1.3. Environmental Influencing Factors -- 19.1.4. Physical Activity and Obesity -- 19.1.5. Medical History -- 19.1.6. Family History of Cancer -- 19.1.7. Biomarkers -- 19.1.8. Genome Wide Association Study -- 19.1.9. Conclusions -- 19.2. CRC Screening and Early Detection in China -- 19.2.1. Introduction -- 19.2.2. The First Population-Based CRC Screening and Prospective Cohort Study in Haining County -- 19.2.3. Cluster Randomization Trial of Sequence Mass Screening for CRC in Jiashan County -- 19.2.4. Validity of Immunochemical Fecal Occult Blood Test and High-Risk Questionnaire in a Population-Based CRC Screening in Hangzhou -- 19.2.5. Conclusion -- 19.3. The Clue of Microbe Pathogens and CRC -- Study on the Carcinogenesis of Microcystin and H. pylori -- 19.3.1. Introduction -- 19.3.2. Epidemiology Survey of Microcystin and H. pylori Prevalence -- 19.3.3. Experimental Study of Molecular Carcinogenesis of Microcystin and H. pylori Molecular Carcinogenesis of Microcystin -- 19.3.4. Molecular Carcinogenesis of H. pylori -- 19.3.5. Activation of Erk1/2 Pathway Was Involved in Carcinogenesis -- 19.3.6. Conclusion -- 19.4. CRC-Related Gene (SNC6/ST13, SNC19/ST14, SNC73) -- 19.4.1. Introduction -- 19.4.2. SNC6/ST13 -- 19.4.3. SNC19/ST14 -- 19.4.4. SNC73 -- 20. Molecular and Cellular Characteristics of Small Cell Lung Cancer: Implications for Molecular-Targeted Cancer Therapy / Hong-Bin Ji -- 20.1. Introduction -- 20.2. Clinical Diagnosis and Staging of SCLC -- 20.3. The Clinical Management of SCLC -- 20.4. Genetic Alteration of SCLC -- 20.4.1. Oncogenes -- 20.4.2. Allelic Loss of Chromosome in SCLC -- 20.4.3. Dys-regulation of Signaling Pathways in SCLC -- 20.5. Transition from SCLC to Its Variants and/or NSCLC -- 20.6. SCLC Metastasis -- 20.7. Drug Resistance of SCLC -- 20.8. Perspective -- 21. Possibility to Partly Win the War Against Cancer / Ming Zuo -- 21.1. Cancer Targeting Gene-Viro-Therapy with Excellent Antitumor Effects -- 21.1.1. The CTGVT with Potent Antitumor Effect -- 21.1.2. Modification of CTGVT by the Use of Two Genes, CTGVT-DG -- 21.1.3. Other Modification of CTGVT -- 21.2. Super Interferon (sIFN-I) with Super Antitumor Effects on Solid Tumor in Animals and in Patients -- 21.2.1.sINF-I with Super Antitumor Effect on Solid Tumor in Animal Models -- 21.2.2.sIFN-I with Super Antitumor Effects on Solid Tumor in Patients -- 21.2.3. Mechanism of sIFN-I Action -- 21.2.4. Discussion concerning the action of IFN or sIFN-I Briefly -- 21.2.5. Summary of sIFN-I -- 21.3. Cytokine-Induced Killer Cell Therapy and its Important Modification -- 21.3.1. Background -- 21.3.2. Characteristics of CIK Cells -- 21.3.3. Clinical Studies of CIK -- 21.3.4. Modification and Future Prospective of CIK -- 21.3.5. Summary of CIK Therapy -- 21.4. Antibody Protein Therapy and Antibody Gene Therapy or Armed Antibody Gene Therapy -- 21.4.1. Antitumor Protein (mAb) Therapy -- 21.4.2. Immune Therapy Steps Up the Attack -- 21.4.3. Antibody Gene Therapy and Armed Antibody Gene Therapy -- 21.5. Cancer Crusade at 40 -- 21.5.1. Introduction: Celebrating an Anniversary / Eliot Marshall -- 21.5.2. Cancer Research and the 90 Billion USD Metaphor / Eliot Marshall -- 21.5.3.Combining Target Drug to Stop Resistant Tumors / Jocelyn Kaiser -- 21.5.4. Exploring the Genomes of Cancer Cells: Progress and Promise / M.R. Stratton -- 21.5.5.A Perspective on Cancer Cell Metastasis / Robert A. Weinberg -- 21.5.6. Cancer Immunoediting: Integrating Immunity's Roles in Cancer Suppression and Promotion / M.J. Smyth -- 21.6. Conclusion.
Print version record.
Includes bibliographical references.
Elsevier
Keywords: Cancer -- Treatment; HEALTH & FITNESS -- Diseases -- Cancer; MEDICAL -- Oncology; Cancer -- Treatment; Neoplasms -- therapy; Research; Electronic books